Sesamolin exerts anti-proliferative and apoptotic effect on human colorectal cancer cells via inhibition of JAK2/STAT3 signaling pathway - Wu, Di; Wang, Xin-Ping; Zhang, Wei (Cellular and Molecular Biology, 2019)
Colorectal cancer (CRC) is a common malignant tumor that seriously threatens human health and quality of life. At present, the search for safe and more effective treatment for CRC has become necessary. The present study investigated the anti-proliferative and apoptotic effects of sesamolin on human colorectal cancer (HCT116) cells, and the underlying mechanism. Cell proliferation was determined using MTT assay, while the expressions of JAK2, STAT3 and p-STA3 were determined using Western blotting. The levels of expression of matrix metalloproteinases-1, 2 and 9 (MMP1, MMP2 and MMP9) were determined using real-time quantitative polymerase chain reaction (qRT-PCR). The degree of migration and invasion of the cells was assessed using wound healing assay. The results of MTT assay showed that sesamolin significantly and time- and dose-dependently inhibited the proliferation of HCT116 cells (p < 0.05). Treatment of HCT116 cells with sesamolin significantly inhibited their migratory ability (p < 0.05). The expressions of p-JAK2 and p-STAT3 were significantly down-regulated 48 h after 20 µM of JAK2 specific inhibitor (AG490) was added to HCT116 cells (p < 0.05). The expression of p-STAT3 was also significantly and dose-dependently down-regulated 6 h after treatment of HCT116 cells with sesamolin (p < 0.05). Sesamolin and AG490 had synergistic effect and their combination significantly down-regulated the expression of p-STAT3, when compared with sesamolin alone (p < 0.05). Treatment of HCT116 cells with sesamolin significantly and dose-dependently reduced the levels of IL-6-induced expressions of MMP-1, MMP-2 and MMP-9 (p < 0.05). These results suggest that sesamolin induces apoptosis in HCT116 cells and prevents cell invasion via inhibition of the JAK2/STAT3 signaling pathway.